MEDB-37. Chemotherapy response prediction by molecular risk factors in metastatic childhood medulloblastoma. (3rd June 2022) - Obrecht, Denise; Bockmayr, Michael Ludwig; Bison, Brigitte; Pfister, Stefan M; Sturm, Dominik; Sahm, Felix; Jones, David T W; Sill, Martin; von Hoff, Katja; Benesch, Martin; Gerber, Nicolas U; von Bueren, André; et al.
Abstract: BACKGROUND: Childhood metastatic medulloblastoma (MB) frequently receive postoperative chemotherapy (CT) before craniospinal irradiation. Some MB show stable (SD) or progressive disease (PD) upon CT. Identification of biomarkers for non-response might allow therapy-modifications. METHODS: Patients registered to the German HIT-MED database (2001–2019) were eligible if they were 4-21 years old at diagnosis of a M2/M3-metastasized MB, received therapy in analogy to the MET-HIT2000-AB4 protocol, had centrally reviewed response assessment after 2 cycles HIT-SKK-CT and DNA-methylation analysis was available. DNA-methylation-based tumor classification and whole chromosomal (WC) losses/gains were derived from DNA-methylation arrays. RESULTS: 51/163 (31.3%) patients (median age: 9.8±4.4 years, median follow-up: 6.2±4.0 years) presented SD/PD during/after HIT-SKK-CT and were classified as non-responder. Response to CT had high predictive value for PFS/OS (5-year PFS responder: 67.9±4.8 %, non-responder: 26.1±6.6%, p<0.01 / 5-year OS responder: 80.0±4.2%, non-responder: 45.9±8.0%, p<0.01). Patients with nonWNT/nonSHH-MB subtype II (response: 7/13), subtype III (response: 6/19) and/or MYC-amplification (n=27, overlap subtype II/III: n=11/8, response: 14/27) were less likely to respond, while all 6 of WNT, 8/9 SHH-TP53-wildtype and 1/1 SHH-TP53-mutant responded (Mann-Whitney-U-test p=0.04). Further, ≥2 WC losses/gains of chromosome 7/8/11 was associated with superior response (n=29/32, others: n=83/131, Mann-Whitney-U-test p<0.01). We identified a very-high-risk-cohort (any two criteria of: <2 WC losses/gains of chromosome 7/8/11, MYC-amplification, MB subtype II, III, V, or VIII, n=94), and a standard-risk-cohort (WNT or any ≥2 WC losses/gains of chromosome 7/8/11, n=37) with 40 vs. 8 % non-response and 44±5/60±5 vs. 79±7/87±6% 5-year PFS/OS (p<0.01/p<0.01), respectively. Non-response in n=32 non-VHR/non-SR-patients was 32% with a 5-years PFS/OS of 60±10/77±8%. CONCLUSION: Molecular information can be helpful to predict response to chemotherapy. Upon validation, this may contribute to improve treatment stratification in metastatic MB.